A randomised comparative study of coconut oil massage for effect on weight change in low birth weight neonates - Mohini, Mohini; Jaipal, Munna Lal; Bisht, Surender Singh; Tyagi, Amita (International Journal of Contemporary Pediatrics, 2021)
Background: Low birth weight (LBW) babies have more the risk of the neurological complications, physiological problems and mental retardation. Topical massage with natural oil is routinely practiced in India. The positive effects of massage are weight gain, improved sleep/wake pattern, decreased the stress, early discharge from the neonatal intensive care unit (NICU), improve the skin integrity and enhanced parent’s infant bonding. Methods:This prospective interventional randomised comparative study was conducted among 64 LBW babies at Paediatric department of Swami Dayanand hospital (SDH), Delhi. Out of which 31 were in intervention group and 33 were in control group. In the intervention group, mothers were encouraged to massage their babies with 10 ml of coconut oil for 15 min, twice a day until 10 days of life. Those allocated to the control group were received care as usual. Weight and head circumference was measured at enrolment and on day 11 in both the groups. Results: Basic characteristics of neonates of intervention and control group were almost similar. Mean weight gain in intervention group was 352.26±101.05 g while it was 209.70±124.66 g in control group (p=0.0001). Similarly mean weight gain velocity was significantly higher in intervention group (32.02±19.19 g/day) as compared to control group (19.09±11.33 g/day, p=0.0001). Conclusions:The present study supports significant increase in weight gain in LBW preterm and term neonates with coconut oil massage. Coconut oil is easily available in the market and it should be recommended to LBW babies for their better weight gain.